Regional Variation in Hemoglobin Distribution Among Individuals With CKD: the ISN International Network of CKD Cohorts. - Canney, Mark; Induruwage, Dilshani; Tang, Mila; Alencar de Pinho, Natalia; Er, Lee; Zhao, Yinshan; Djurdjev, Ognjenka; Ahn, Yo Han; Behnisch, Rouven; Calice-Silva, Viviane; Chesnaye, Nicholas C.; de Borst, Martin H.; et al. (Kidney International Reports, 2023)
INTRODUCTION: Despite recognized geographic and sex-based differences in hemoglobin in the general population, these factors are typically ignored in patients with chronic kidney disease (CKD) in whom a single therapeutic range for hemoglobin is recommended. We sought to compare the distribution of hemoglobin across international nondialysis CKD populations and evaluate predictors of hemoglobin. METHODS: In this cross-sectional study, hemoglobin distribution was evaluated in each cohort overall and stratified by sex and estimated glomerular filtration rate (eGFR). Relationships between candidate predictors and hemoglobin were assessed from linear regression models in each cohort. Estimates were subsequently pooled in a random effects model. RESULTS: A total of 58,613 participants from 21 adult cohorts (median eGFR range of 17-49 ml/min) and 3 pediatric cohorts (median eGFR range of 26-45 ml/min) were included with broad geographic representation. Hemoglobin values varied substantially among the cohorts, overall and within eGFR categories, with particularly low mean hemoglobin observed in women from Asian and African cohorts. Across the eGFR range, women had a lower hemoglobin compared to men, even at an eGFR of 15 ml/min (mean difference 5.3 g/l, 95% confidence interval [CI] 3.7-6.9). Lower eGFR, female sex, older age, lower body mass index, and diabetic kidney disease were all independent predictors of a lower hemoglobin value; however, this only explained a minority of variance (R2 7%-44% across cohorts). CONCLUSION: There are substantial regional differences in hemoglobin distribution among individuals with CKD, and the majority of variance is unexplained by demographics, eGFR, or comorbidities. These findings call for a renewed interest in improving our understanding of hemoglobin determinants in specific CKD populations.
EVALuna2:545788